Sintesis Asam-Asam Lemak Hidroksamik dari Minyak Kelapa Menggunakan Lipase sebagai Katalis - Suhendra, Dedy; Gunawan, Erin Ryantin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
Fatty hydroxamic acids (FHAs) have been successfully synthesized from coconut oil by a one-step lipase catalyzed reaction. FHAs are theacids that are based on fatty acids. Their hydrophobicity can be use for some applications such as surfactant and metal ions extraction fromaqueous media. This paper describes enzymatic synthesis of FHAs from coconut oil by reacting hydroxylamine with the substrate catalyzedby a lipase. The lipase used was Lipozyme, a commercially lipase of Mucor meihe fixed on a polymer anion exchange resin. The use ofimmobilized lipase as the catalyst for the preparation reaction provides an easy isolation of the enzyme from the products and othercomponents in the reaction mixture. In addition, it also allows the reaction to be carried out under mild conditions, which reduces thereaction’s side products. The optimum preparation conditions obtained were as follows; the reaction temperature was 30 oC, the reactiontime was 30 h, the ratio of coconut oil : lipozyme (g : g) was 29.5, and the ratio of hydroxylamine : coconut oil (mmol : mmol) was 6. Thesolvent used was hexane. The purified products were characterized by qualitative test, such as FTIR spectroscopy and HPLC.